The presence and danger of microplastics in the oceans - Margeta, Amalija (Array, 2021)
Since the environmental pollution by microplastics is a relatively new area of research, the main problem is the lack of appropriate rules, regulations and parameters globally. Therefore, the sources of primary and secondary microplastics particles vary from source to source, and due to this the difference in the division of microplastic particles by size arises too. Moreover, various techniques and technologies are used when testing seawater and sediment as well. Ultimately, with different qualities of the obtained results, it leads to difficult and/or inadequate comparison. Furthermore, the research has been mainly conducted on smaller marine organisms, which needs to be extended to other larger organisms as well as to the human population to create a complete image of the negative effects of contamination of the marine food chain and the marine environment with microplastic particles in general.